Análise de pesticidas em sedimentos de um lago urbano em Francisco Beltrão – PR - Baltazar, Guilherme Henrique da Silva (2023)
Pesticides have long been used by humans to combat crop pests, but the consequences of excessive use have not been evaluated. Even today, the use of these chemical substances is disordered, however many topics and discussions are raised about the problem. Countless studies, in different matrices (air, water, soil, sediments, etc.), evaluate the contamination rate to assimilate the threats of these compounds involving the Environment and human health. That said, this work sought to quantify the concentration of three organochlorine pesticides (Aldrin, Dieldrin and 4,4'-DDT) and an organophosphate (Glyphosate), in sediment samples from an urban lake located in Francisco Beltrão – PR, and evaluate the associated ecological risk, as well as identifying possible sources of contamination according to land use and occupation over time. Samples were collected every two months, between November 2021 and March 2022, at three collection points and in duplicates, totaling eighteen samples. In the extraction process, an adaptation of the QuEChERS method was used, without the clean up step. For the analysis of organophosphate, a Liquid Chromatograph Coupled with Mass Spectroscopy (LC-MS/MS) was used, while for organochlorine a Gas Chromatograph with Mass Spectrometry Detection (GC-MS/MS) was used. In general, organochlorine pesticides have not been quantified and there are no ecological risks. Glyphosate concentrations demonstrate that the contamination is recent, as its degradation product, AMPA, was not detected, however there are no significant risks to the benthic community. The entry of Glyphosate into the environment may be related to its use in controlling weeds in urban areas, as well as the entry of contaminated sediments during periods of flooding of the Marrecas River, which floods the lake.